Encapsulation-Dependent Enhanced Emission of Near-Infrared Nanoparticles Using in vivo Three-Photon Fluorescence Imaging - Du, Ye; Alifu, Nuernisha; Wu, Zhiyuan; Chen, Runze; Wang, Xiaozhen; Ji, Guang; Li, Qian; Qian, Jun; Xu, Bin; Song, Dong (Frontiers in Bioengineering and Biotechnology, 2020)
We discovered a unique fluorescent enhancement of dye encapsulated polymeric nanoparticles, which strongly depended on the polymeric matrix. Interestingly, the polymer nanoparticles containing a NIR emissive dye exhibited remarkable enhancement of emission encapsulated by the polymer amphiphilic polymer containing polystyrene (PS) moiety, whereas the nanoparticles showed weak fluorescence when using other polymer encapsulation. The highest fluorescent quantum yield of nanoparticles can reach 27% by using PS-PEG encapsulation, where the strong NIR fluorescence can be observed. These ultra-bright fluorescence nanoparticles also possess a strong three-photon fluorescence and show a good candidate for in vivo vascular three-photon fluorescence imaging of mouse brain and ear under 1550 nm fs laser excitation. A fine three-dimensional (3D) reconstruction with an imaging depth of 635 μm and 180 μm was achieved, respectively. We further demonstrate that these nanoparticles can effectively target the sentinel lymph node (SLN) of mice.